This I Believe - Stewart, Irvin (Tufts Archival Research Center, 2006)
Irvin Stewart describes how he believes life resembles a newsreel of a football game: like the camera lens, our perspective is limited to a narrow section of the whole field, even though we are still playing a role in the greater cooperative enterprise.